Is the Clinical Version of the Iowa Gambling Task Relevant for Assessing Choice Behavior in Cases of Internet Addiction? - Lin, Ching-Hung; Wang, Chao-Chih; Sun, Jia-Huang; Ko, Chih-Hung; Chiu, Yao-Chu (Frontiers in Psychiatry, 2019)
Objective: A critical issue in research related to the Iowa gambling task (IGT) is the use of the alternative factors expected value and gain-loss frequency to distinguish between clinical cases and control groups. When the IGT has been used to examine cases of Internet addiction (IA), the literature reveals inconsistencies in the results. However, few studies have utilized the clinical version of IGT (cIGT) to examine IA cases. The present study aims to resolve previous inconsistencies and to examine the validity of the cIGT by comparing performances of controls with cases of Internet gaming disorder (IGD), a subtype of IA defined by the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders. Methods: The study recruited 23 participants with clinically diagnosed IGD and 38 age-matched control participants. Based on the basic assumptions of IGT and the gain-loss frequency viewpoint, a dependent variables analysis was carried out. Results: The results showed no statistical difference between the two groups in most performance indices and therefore support the findings of most IGT-IA studies; in particular, expected value and gain–loss frequency did not distinguishing between the IGD cases and controls. However, the participants in both groups were influenced by the gain-loss frequency, revealing the existence of the prominent deck B phenomenon. Conclusion: The findings provide two possible interpretations. The first is that choice behavior deficits do not constitute a characteristic feature of individuals who have been diagnosed with IGD/IA. The second is that, as the cIGT was unable to distinguish the choice behavior of the IGD/IA participants from that of controls, the cIGT may not be relevant for assessing IGD based on the indices provided by the expected value and gain-loss frequency perspectives in the standard administration of IGT.